Strategi Pengembangan Usahatani Tomat Di Desa Tambelang Kecamatan Maesaan Kabupaten Minahasa Selatan - Goni, Wanda; Rori, Yolanda Pinky Ivanna; Memah, Melsje Yellie (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the development strategy of tomato farming in Tambelang Village, Maesaan District, South Minahasa Regency. The research was conducted for 3 months, from December 2022 to January 2023. The location of the research was Tambelang Village, Maesaan District, South Minahasa Regency, North Sulawesi Province. The data used in this study were primary data obtained through interviews using questionnaires while secondary data were obtained from journals and theses. The data collection methods used in the research were observation, interview, and documentation. The data analysis method uses SWOT analysis. The results of this study indicate that all indicators of tomato development in Tambelang Village have strengths to develop. It can be seen from the results of the analysis on the SWOT matrix that the coordinates are 0.36 - 0.5, which shows that these coordinates are in quadrant 1, namely supporting the growth strategy, which means being in very favorable conditions. It is said to be very profitable because it has strengths so that it can take advantage of business opportunities to be managed in the best way with a strategy to support significant growth (Growth oriented strategy).